Antimalarial drugs and pregnancy: safety, pharmacokinetics, and pharmacovigilance. - Ward, SA; Sevene, E; Hastings, I; Nosten, F; Mcgready, R (2007)
Before a recommendation for antimalarial drug use in pregnancy is made, it is essential that we understand the potential risks involved and have mechanisms in place to monitor risk during treatment. This requires data on drug disposition during pregnancy and potential toxicological liabilities to the developing fetus and mother. In most cases this information is not available. We review the reproductive toxicology of the main antimalarial drug classes in use or under development. Preclinical data are presented if appropriate, but as human experience overrides such data, in instances in which preclinical studies do not correlate with the human experience the data are reviewed only briefly. Additionally, we highlight the lack of appropriate drug disposition data in pregnancy and suggest mechanisms that can be used to capture data on risk after drug treatment in pregnancy.